THE EFFECT OF MILLING TIME AND PERCENTAGE OF DISPERSING AGENT ON THE CHARACTERISTIC OF SOLVENT-BASED BLACK PAINT FROM CARBON BLACK PIGMENT - Ratnawati Ratnawati; Joko Noveriarto; Aniek S Handayani; Is S Purwaningsih; Iyus Hendrawan (Jurnal Sains Materi Indonesia, 2020)
THE EFFECT OF MILLING TIME AND PERCENTAGE OF DISPERSING AGENT ON THE CHARACTERISTIC OF SOLVENT-BASED BLACK PAINT FROM CARBON BLACK PIGMEN. The need for black paint made from carbon black pigment increasing year by year especially in the automotive world. The production of black paint is performed by milling the resin, pigment, additive/dispersing agent, and solvent. In the manufacturing process, it takes a relatively long time with precise dispersing agent composition toward pigment to get the product with blackness/solid black according to the expected quality. This work aims to study the role of the milling time of carbon black fw 200 beads on a 3 liter ball mill and the percentage of dispersing agents on paint color quality, especially blackness. The variations in milling time were 36, 48, and 60 hours and the weight percentage of dispersing agent toward pigment were 80%, 100%, and 120%. The optimum results obtained are at the milling time of 48 hours and on the percentage of dispersing agent of 120% with the product characteristics fulfills the requirement namely: 10 μm of particle fineness, 111.5 krebs unit of viscosity, 36.97% of solid content, 0.9839 gr/cc of specific gravity with desirable solid black color.